Minin Nizhny Novgorod State Pedagogical University - Elena V. Myalkina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки, 2019)
The work is devoted to the analysis of the development of the system of continuous professional education in Russia and abroad in various historical periods. The article analyzes the stages of development of the system of continuous education, the mainfactors affecting its development, comparable reasons. The study of the process of development of the system of continuous education allows to highlight the problems ofits formation at various stages. Modern society emphasizes the special role of education as the leading value of preserving and enhancing culture and the growth of human potential. Continuing education in such conditions is of particular relevance because it goes beyond the formal education, covering various groups of the population, more than other forms of education, providing self-realization and self-expression ofthe individual. Considering the main stages of the development of the system of continuous education, we can trace its subordination to the various priorities of the development of the state system: the development of the country’s industrial potential, political education and ideological propaganda, raising the cultural level of citizens. In this case can trace the vector of society’s influence on the system of lifelong education, which forms an actual order for educational topics: health protection, familiarity with new technologies, individual creative self-development.The study of the process of development of the system of continuous education allowed us to conclude about its significant role in the modern educational space, to identify its functions - professional, personal, social, to formulate the leading ideas for the development of continuing education in modern conditions.